2012
DOI: 10.1155/2012/210756
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gamma-Secretase for the Treatment of Alzheimer's Disease

Abstract: The Amyloid Hypothesis states that the cascade of events associated with Alzheimer's disease (AD)—formation of amyloid plaques, neurofibrillary tangles, synaptic loss, neurodegeneration, and cognitive decline—are triggered by Aβ peptide dysregulation (Kakuda et al., 2006, Sato et al., 2003, Qi-Takahara et al., 2005). Since γ-secretase is critical for Aβ production, many in the biopharmaceutical community focused on γ-secretase as a target for therapeutic approaches for Alzheimer's disease. However, pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…The deterioration, which presumably resulted from semagacestat-induced collateral damage to other proteins affecting neurocognitive function [18], persisted after the drug was stopped. It is now known that TP was on placebo during at least the initial twelve months of the study.…”
Section: Clinical Response Of a Patient With Ad Dementia To Kme Trmentioning
confidence: 99%
“…The deterioration, which presumably resulted from semagacestat-induced collateral damage to other proteins affecting neurocognitive function [18], persisted after the drug was stopped. It is now known that TP was on placebo during at least the initial twelve months of the study.…”
Section: Clinical Response Of a Patient With Ad Dementia To Kme Trmentioning
confidence: 99%
“…Next, it is thought that γ-secretase further cleaves the Aβ fragment every other 3 or 4 amino acids from the ζ-site to the γ-site until the Aβ fragment is freed from the membrane [70]. This leads to the production of Aβ fragments of varying sizes, from 37 to 46 amino acids in length (with heterogeneous C-termini), including neurotoxic Aβ(1-42), which can easily oligomerize and become more prone to aggregation [72]. Furthermore, mutations in APP and the PS1 protein in γ-secretase can lead to changes in this cleavage pattern [71].…”
Section: 0 App Processingmentioning
confidence: 99%
“…The compounds in this series, including SPI-1865, have a novel and proprietary structure, as well as the unique effect on the Aβ profile of lowering both Aβ 42 and Aβ 38 , without effecting Aβ 40 in cellular systems [33]. Using immunoprecipitation/mass spectrometry (IP/MS) analysis of conditioned media from Satori compound-treated versus control 2B7 cells, it was observed that the total Aβ levels are maintained with concomitant lowering of Aβ 38 and Aβ 42 and increases in Aβ 37 and Aβ 39 [34]. Furthermore, since increasing substrate levels do not result in an IC 50 shift, it is likely that SPI-1865 binds to the gamma-secretase complex as do other GSMs [35-37] instead of the APP substrate [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Using immunoprecipitation/mass spectrometry (IP/MS) analysis of conditioned media from Satori compound-treated versus control 2B7 cells, it was observed that the total Aβ levels are maintained with concomitant lowering of Aβ 38 and Aβ 42 and increases in Aβ 37 and Aβ 39 [34]. Furthermore, since increasing substrate levels do not result in an IC 50 shift, it is likely that SPI-1865 binds to the gamma-secretase complex as do other GSMs [35-37] instead of the APP substrate [33,34]. In the studies described here, the effects of SPI-1865 on Aβ 38 , Aβ 40 and Aβ 42 in both wild-type and transgenic animals were examined.…”
Section: Introductionmentioning
confidence: 99%